2016
DOI: 10.1016/j.npep.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y (NPY) in tumor growth and progression: Lessons learned from pediatric oncology

Abstract: Neuropeptide Y (NPY) is a sympathetic neurotransmitter with pleiotropic actions, many of which are highly relevant to tumor biology. Consequently, the peptide has been implicated as a factor regulating the growth of a variety of tumors. Among them, two pediatric malignancies with high endogenous NPY synthesis and release – neuroblastoma and Ewing sarcoma – became excellent models to investigate the role of NPY in tumor growth and progression. The stimulatory effect on tumor cell proliferation, survival and mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 108 publications
(254 reference statements)
0
69
0
1
Order By: Relevance
“…NPY is widely expressed in the central and peripheral nervous system, influencing via its Y receptors many physiological processes, such as cortical excitability, stress and immune response, food intake, circadian rhythms, cardiovascular function, glucose metabolism. NPY is also involved in biology of some tumors, controlling angiogenesis, tumor growth, metastasis and cancer cell metabolism [84]. An in vitro study revealed that Y1 and Y2 receptors are present in the androgen-independent human PC-3 cell line and that their activation by NPY stimulates cancer cell proliferation, which suggests its impact on castration-resistant regulation of PC [83,85].…”
Section: Nt In Pcmentioning
confidence: 99%
“…NPY is widely expressed in the central and peripheral nervous system, influencing via its Y receptors many physiological processes, such as cortical excitability, stress and immune response, food intake, circadian rhythms, cardiovascular function, glucose metabolism. NPY is also involved in biology of some tumors, controlling angiogenesis, tumor growth, metastasis and cancer cell metabolism [84]. An in vitro study revealed that Y1 and Y2 receptors are present in the androgen-independent human PC-3 cell line and that their activation by NPY stimulates cancer cell proliferation, which suggests its impact on castration-resistant regulation of PC [83,85].…”
Section: Nt In Pcmentioning
confidence: 99%
“…As such it modulates many physiological functions ranging from stress responses, food intake, reproduction, circadian rhythms, anxiety and depression and pain processing (64). It exerts its principal activities through neuropeptide receptors 1, 2 and 5 and in the context of cancer (65), much information has been learned from two pediatric diseases with high endogenous NPY production-neuroblastoma and Ewing sarcoma-that have become models to investigate the role of NPY in tumor growth and progression (66). However, NPY and its receptor have been found to be expressed in cells and vasculatures from a variety of tumors (65) where they exert complex effects.…”
Section: Npymentioning
confidence: 99%
“…However, NPY and its receptor have been found to be expressed in cells and vasculatures from a variety of tumors (65) where they exert complex effects. It is generally accepted that NPY is an angiogenic factor, which strongly induces the endothelial cell proliferation, differentiation and migration, and promotes vascularization (66). Aside from being synthesized in tumor cells, NPY is also released systemically from sympathetic neurons (67).…”
Section: Npymentioning
confidence: 99%
See 1 more Smart Citation
“…While well regarded as an orexigenic peptide in the brain, NPY functions in many other aspects of physiology, such as learning and memory, 102 tumor growth and progression, 103 and other processes related to adipose tissue. The effects of NPY that are related to adipose tissue and energy balance are summarized in Table 2 and Figure 1.…”
Section: Adipose Physiology: Npymentioning
confidence: 99%